Cluster of Coronavirus Disease 2019 (COVID-19) in the French Alps, February 2020. (11th April 2020) - Danis, Kostas; Epaulard, Olivier; Bénet, Thomas; Gaymard, Alexandre; Campoy, Séphora; Botelho-Nevers, Elisabeth; Bouscambert-Duchamp, Maude; Spaccaferri, Guillaume; Ader, Florence; Mailles, Alexandra; Boudalaa, Zoubida; Tolsma, Violaine; et al.
Abstract: Background: On 7 February 2020, French Health authorities were informed of a confirmed case of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in an Englishman infected in Singapore who had recently stayed in a chalet in the French Alps. We conducted an investigation to identify secondary cases and interrupt transmission. Methods: We defined as a confirmed case a person linked to the chalet with a positive reverse-transcription polymerase chain reaction sample for SARS-CoV-2. Results: The index case stayed 4 days in the chalet with 10 English tourists and a family of 5 French residents; SARS-CoV-2 was detected in 5 individuals in France, 6 in England (including the index case), and 1 in Spain (overall attack rate in the chalet: 75%). One pediatric case, with picornavirus and influenza A coinfection, visited 3 different schools while symptomatic. One case was asymptomatic, with similar viral load as that of a symptomatic case. Seven days after the first cases were diagnosed, 1 tertiary case was detected in a symptomatic patient with from the chalet a positive endotracheal aspirate; all previous and concurrent nasopharyngeal specimens were negative. Additionally, 172 contacts were monitored; all contacts tested for SARS-CoV-2 (N = 73) were negative. Conclusions: The occurrence in this cluster of 1 asymptomatic case with similar viral load as a symptomatic patient suggests transmission potential of asymptomatic individuals. The fact that an infected child did not transmit the disease despite close interactions within schools suggests potential different transmission dynamics in children. Finally, the dissociation between upper and lower respiratory tract results underscores the need for close monitoring of the clinical evolution of suspected cases of coronavirus disease 2019. Abstract : In this cluster, 12 COVID-19 cases (1 asymptomatic) were linked to a single index case. One child, coinfected with other respiratory viruses, attended 3 schools while symptomatic but did not transmit the virus, suggesting potential different transmission dynamics in children.